Neuroprotective Effects of A Standardized Flavonoid Extract of Safflower Against Neurotoxin-Induced Cellular and Animal Models of Parkinson’s Disease - Rutong Ren; Chunyan Shi; Jing Cao; Yi Sun; Xin Zhao; Yongfei Guo; Chen Wang; Hui Lei; Hanjie Jiang; Nuramatjan Ablat; Jiamin Xu; Wan Li; et al. (2016)
Abstract Safflower has long been used to treat cerebrovascular diseases in China. We previously reported that kaempferol derivatives of safflower can bind DJ-1, a protein associated with Parkinson’s disease (PD) and flavonoid extract of safflower exhibited neuroprotective effects in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced mouse model of PD. In this study, a standardized safflower flavonoid extract (SAFE) was isolated from safflower and mainly contained flavonoids. Two marker compounds of SAFE, kaempferol 3-O-rutinoside and anhydrosafflor yellow B, were proven to suppress microtubule destabilization and decreased cell area, respectively. We confirmed that SAFE in dripping pill form could improve behavioural performances in a 6-hydroxydopamine (6-OHDA)-induced rat model of PD, partially via the suppression of α-synuclein overexpression or aggregation, as well as the suppression of reactive astrogliosis. Using an MRI tracer-based method, we found that 6-OHDA could change extracellular space (ECS) diffusion parameters, including a decrease in tortuosity and the rate constant of clearance and an increase in the elimination half-life of the tracer in the 6-OHDA-lesioned substantia nigra. SAFE treatment could partially inhibit the changes in ECS diffusion parameters, which might provide some information about neuronal loss and astrocyte activation. Consequently, our results indicate that SAFE is a potential therapeutic herbal product for treatment of PD.